Bernard Mark, powstanie w getcie warszawskim i proces Jürgena Stroopa - Finder, Gabriel (Zagłada Żydów. Studia i Materiały, 2017)
Jürgen Stroop, the SS general who led the liquidation of the Warsaw Ghetto and the suppression of the Warsaw Ghetto Uprising in April–May 1943, was convicted by a Polish court in 1951 and executed in 1952. Bernard (Ber) Mark (1908–1966), Holocaust historian and director of the Jewish Historical Institute in Warsaw, provided expert testimony for the prosecution at Stroop’s trial. Mark felt constrained to graft a communist-inflected narrative onto his account of the Warsaw Ghetto Uprising and to shoehorn it into his expert testimony in court and then into his interpretation of the trial for a Jewish audience. He did his best to give the Jewish Fighting Organization, which spearheaded the uprising, and its Jewish fighters their due at a time when expression of unvarnished appreciation for Jewish heroism was risky, even while he was paying overrated tribute to the communist underground for its assistance to the Jewish rebels during the uprising. But he always stopped short of the line between conformity to and defiance of the communist regime